Towards Reviving the Missing Noble Characteristics of Traditional Habitual Social Life: “Al-Farej “In Kingdom of Bahrain - ISLAM H. EL-GHONAIMY; MARIAM HAIDER AL-HADDAD (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
For a long time, Social life in Bahrain was unique and positive. Public Participation and social cooperative with no reference of segregation or discrimination for a long time. Regularly residences were gathering together to discuss the daily life, solving problems, discussing their economic and social issues with a spirit of respecting human rights and civilization. In Bahrain, there were many elements, which were positively in city quality of life. The research problem is that, unfortunately, most of the old part of Manama city, Capital of Bahrain, area suffer from losing the identity by modernization in many forms by urban developing. Consequently, day by day, the social life became different and lost most of noble characteristics of traditional habitual Social life. Bahraini heritage alive in the old area of Manama City, the area needs a node and a reference point for the community to gather in a better-built environment. Therefore, there is an essential need for proposing a solution to revive the brilliant of social life in Kingdom of Bahrain in term of gathering people for cultural events with the economic return to keep the rich history and importance of the area and enhance the environment of the center of Manama. The aim of the research is to propose a solution to solve the missing of social life in the old part of Bahrain by giving guidelines in representing “Al-Farej” in a modern way matching with the modernization of life in Manama.